Development of a tool to evaluate clinical teaching performance of 2nd year faculty of the Dela Salle University Health Sciences Campus-College of Medicine - Babao-Balgomera, Nune (2001)
The Dela Salle University Health Sciences Campus-College of Medicine (DLSUHSC-CM), has undergone tremendous changes and growth in the student population, the faculty, and the infrastructure since its inception in 1979 as Emilio Aguinaldo College of Medicine. To answer the increasing needs of the institution brought about by these changes, the administration initiated several moves which included the establishment of an Academic Personnel Evaluation Board (APEB) in 1993 which was tasked to implement a teacher evaluation plan. In conjunction with these, the criteria for faculty evaluation has been developed and revised but it has left out the evaluation of clinical teaching. It is the objective of this paper therefore, to come up with a valid, practical and reliable tool for this purpose in the hope of improving the faculty performance in clinical teaching particularly Physical Diagnosis (PD). The expected improvement in clinical teaching that may be brought about by analysis of the results of the evaluation may hopefully contribute to facilitation of student learning. The use of student questionnaire in the evaluation of teaching is now commonplace and has been proven by various researches to be valid, reliable and practical. It is also highly acceptable in DLSUHSC-CM because it is economical and relatively easy to administer. Furthermore, student opinions and evaluations are given a high premium and has been the only source of evaluation data for the past decade in the same institution. Thus, the researcher chose to develop a student rating scale. The first draft of the student rating scale was developed using the characteristics of an effective clinical teacher as reported by various experts as bases in concurrence with the list of tasks of PD preceptors. The questionnaire consisted of twenty four statements reflecting clinical teaching behaviors expected of a 2nd year PD clinical preceptor clustered into three major concepts namely: clinical supervision, clinical competence, and interpersonal relationship. This was sent to six (6) PD preceptors and fifteen (15) students to establish content validity using the Delphi Technique. The comments by the two stakeholder groups were taken into consideration in the revision of the tool. The revised instrument was field-tested to thirty (30) incumbent 2nd year medical students. The data that was gathered was subjected to factor analysis. Results of factor analysis showed that all items are measuring one core concept or dimension which pertains to the primary tasks of PD preceptors foremost of which are as follows: demonstration of skills and return demo; provision of adequate and closely supervised practice opportunities; and provision of an ideal role model. Due to this result the categorization of the items were deleted in the final instrument. Modified content validity was then performed by comparing the final tool with various published and unpublished clinical evaluation tools which revealed similar contents. The final tool was administered to the study population which consisted of 115 students or fifty percent of the second year class for school year 2000-2001. The instrument's practicality was also determined. The average time spent by a respondent to finish the questionnaire was ten minutes. Reliability testing was performed on the data from the final tool. Results showed a high Cronbach's alpha coefficient for all items indicating that the instrument is reliable. This is also supportive of the validity of the tool. It is recommended therefore, that the developed instrument be used as a formative evaluation tool of clinical teaching performance of PD preceptors at DLSUHSC-CM. Analysis of the results will hopefully lead to the development of specific action plans designed to provide feedback and help teachers improve their performance. It is also recommended that further validity and reliability studies be conducted on the instrument.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Clinical medicine -- Study and teaching